Cyberactivism in South Cotabato a co-cultural analysis of the online #DefendTampakan movement of environmentalists in upholding the mining ban in Tampakan, South Cotabato - Dimalanta, Raphael John P.
Cyberactivism is a powerful tool for promoting social change, especially among oppressed communities (Carty & Barron, 2019). This study examined the use of cyberactivism by the #DefendTampakan movement led by a group of environmentalists from South Cotabato, Philippines, who are utilizing social media platforms to pronounce their stand against the proposed open-pit mining project in Tampakan.?The study used a co-cultural perspective to analyze the #DefendTampakan?s online movement. This allows for the researcher to position the environmentalists as a co-cultural group who would use social media platforms as a counter-hegemonic tool to navigate communication barriers online. Methdologies of the study included key informant interviews among the co-cultural group and a netnographic analysis of the #DefendTampakan network from December 2021 to June 2022 to identify the communication strategies used and the perceived impacts of these strategies. The study surfaced strategies such as educating and raising awareness about the risks of open-pit mining, subverting pro-mining narratives, building solidarity with other groups, utilizing social media platforms during the pandemic, and employing a pluralist/multisectoral approach. The #DefendTampakan movement was able to achieve a number of perceived impacts, including delays on the mining project, establishment of principled alliances, and widened reach of the movement due to social media coverage. These findings suggest that cyberactivism can be a powerful tool for promoting social change, however there is a need for future considerations to employ an intersectionality approach in evaluating the quality and effectiveness of the communication strategies.